Impact of impaired executive function on gait stability. - Allali G; Assal F; Kressig RW; Dubost V; Herrmann FR; Beauchet O (Dementia & Geriatric Cognitive Disorders, 2008)
Background: Executive dysfunction contributes to gait changes, but the precise mechanisms are still poorly understood. Dual-task-related gait changes depend in part on the capacity to appropriately allocate attention between tasks performed simultaneously and are mainly related to executive deficits. This study aimed to describe the impact of dysexecutive function on gait stability in subjects with dementia using dual tasking. Methods: Mean values and coefficients of variation of stride time while only walking and while walking and backward counting (dual tasking) were measured using the GAITRite® System in 18 subjects with dementia and impaired executive function (IEF), in 16 subjects with dementia and intact executive function, and in 22 nondemented subjects as controls. Results: Stride time, and particularly its variability, significantly increased while performing dual tasking (p < 0.05). IEF was related to both stride time and stride time variability during walking only and to even more gait changes, while dual tasking compared to nondemented subjects and demented subjects without IEF. Conclusions: These findings confirm the role of executive function in dual tasking, but also strongly suggest their importance for gait stability.